New experimental measurements of the H2-CO2 Collision-Induced Absorption in the [3907, 4770] cm−1 spectral range from 241 to 498 K - F. Vitali; S. Stefani; G. Piccioni; H. Tran; M. Snels; D. Grassi; C. Boulet; D. Biondi; A. Boccaccini (Icarus, 2026)

Investigation of the impacts of second-generation antihistamines on free-living marine nematodes and their interaction with ZnS nanoparticles: Mechanistic insights from community and population approaches and molecular interactions modeling - Samir Ghannem; Houcine Labiadh; Sahar Ishak; Sonia Louiz; Assia Derguini; Takfarinas Idres; Eleonora Grassi; Federica Semprucci; Riadh Badraoui; Naoufel Ben Hamadi; Anis A. Chaudhary; Sulaiman A. Alsalamah; et al. (Marine Environmental Research, 2026)

Bacteria associated with spores of arbuscular mycorrhizal fungi: a review - Monica Agnolucci; Arianna Grassi; Manuela Giovannetti; Olga A. Lastovetsky (Biology and Fertility of Soils, 2026)
Arbuscular mycorrhizal fungi (AMF) are important components of terrestrial ecosystems and sustainable agricultural practices, forming mutually beneficial symbiotic associations with roots of most land plants including crops by providing them with nutrients in exchange for photosynthesis-derived carbon and protection from biotic and abiotic stresses. Microorganisms, including bacteria, are emerging as important new players in the AMF-plant symbiosis by influencing symbiotic outcome. Specifically, bacteria can tightly associate with AMF extraradical mycelium and spores. Spores are produced mainly in the soil and function in reproduction and dissemination. Spores are large and full of lipids and therefore represent an important soil carbon pool as well as an attractive niche for soil bacteria, termed the “sporosphere”. Intriguingly, diverse bacterial communities have been found in different parts of the sporosphere environment, and they may possess roles in complementing and enhancing AMF function. In this review, we describe the AMF sporosphere environment and summarize our current knowledge of spore-associated bacterial communities including their composition, assembly, function and localization. We also identify knowledge gaps and future research directions as well as highlight spores as model systems for studying AMF–microbe interactions.

Adventively established Leptopilina japonica: a new opportunity for augmentative biocontrol of Drosophila suzukii - Marco Valerio Rossi-Stacconi; Paul K. Abram; Gianfranco Anfora; Elizabeth Beers; Antonio Biondi; Nicolas Borowiec; Juli Carrillo; Jana Collatz; Asia Colmagro; Benjamin Crossman Johnson; Kent Daane; Giovanni Dal Zotto; et al. (Journal of Pest Science, 2025)
The invasive spotted-wing drosophila, Drosophila suzukii , has emerged as a significant global pest over the past decade, threatening fruit production worldwide. The parasitoid Leptopilina japonica , presumed native to East Asia, has established adventive populations in Europe and North America and is increasingly recognized for its ability to parasitize substantial proportions of D. suzukii larvae across diverse habitats. Here, we provide a broad review of the biology, establishment, distribution, and potential impacts of L. japonica . Using field data from international monitoring programs, we document the seasonal dynamics of plant–host–parasitoid associations and assess evidence for L. japonica ’s impact on D. suzukii and non-target organisms. Findings indicate that L. japonica has successfully established in several areas where D. suzukii is present in Europe and North America, showing promise as a biological control agent to support sustainable pest management. Current data suggest it provides some suppression of D. suzukii populations with minimal non-target effects. However, long-term studies are necessary to clarify its food web interactions and efficacy as a biological control agent. In areas where L. japonica has been established, we propose its use in augmentative biological control programs to enhance its impacts in specific agricultural settings. Case-specific evaluations of its ecological effects and role in integrated pest management, supported by continued monitoring, are essential. The case of L. japonica illustrates the need for clear, research-informed policies to guide the use of adventively established non-indigenous natural enemies in pest management.

Effects of antibiotics and metals on meiofauna assessed through taxon/functional and modeling tools: a case study of amoxicillin and copper - Sahar Ishak; Samir Ghannem; Renad M. Alotaibi; Rahaf S. Alkatheri; Mona F. Alharbi; Alanood M. Almutrif; Eleonora Grassi; Federica Semprucci; Riadh Badraoui; Sunakbaeva Dilara; Naoufel Ben Hamadi; Lotfi Khezami; et al. (Marine Pollution Bulletin, 2025)

Attenuation of Cellular Senescence and Improvement of Osteogenic Differentiation Capacity of Human Liver Stem Cells Using Specific Senomorphic and Senolytic Agents - Allancer D. C. Nunes; Louise E. Pitcher; Henry A. Exner; Diego J. Grassi; Brittan Burns; Maria Beatriz Herrera Sanchez; Ciro Tetta; Giovanni Camussi; Paul D. Robbins (Stem Cell Reviews and Reports, 2025)
Expansion of adult stem cells in culture increases the percent of senescent cells, reduces their differentiation capacity and limits their clinical use. Here, we investigated whether treatment with certain senotherapeutic drugs would reduce the accumulation of senescent cells during expansion of human liver stem cells (HLSCs) while maintaining their differentiation capacity. Our results demonstrate that chronic treatment with the senomorphic XJB-5-131 or the senolytics cocktail D + Q reduced the number of senescent cells and significantly reduced the expression of senescence-associated genes and several inflammatory SASP factors in later passage HLSCs. Additionally, treatment with XJB-5-131 and D + Q improved the capacity of HLSCs to undergo osteogenic differentiation following extensive in vitro expansion. Overall, our data demonstrate that treatment with XJB-5-13 or D + Q results in a reduction in the percentage of replication-induced senescent HLSCs and likely other types of adult stem cells and improve the potential therapeutic use of later passage human stem cells. Graphical abstract

Elucidating mechanisms of action of environmental contaminants from Doce River in Brazilian fish embryos using metabolomics and chemometric methods - Flávia Y. Yamamoto; Larissa A. Batista; Mayara P. Santos; Carmen Bedia; Silvia Lacorte; Rivelino M. Cavalcante; Marco T. Grassi; Denis M. de Souza Abessa; Romà Tauler (Science of The Total Environment, 2025)

Deformed archaeological remains at Lilybaeum in Western Sicily (southern Italy): possible ground signatures of a missed large earthquake - G. Barreca; F. Pepe; A. Sulli; G. Morreale; S. Gambino; M. Gasparo Morticelli; S. Grassi; C. Monaco; S. Imposa (Natural Hazards, 2025)
Archaeoseismic analysis performed in Western Sicily points to deformed archeological remains at Lilybaeum , a Punic coastal city founded in 397 B.C. at the Island’s westernmost edge. Starting from the direct observation of deformed ruins, an interdisciplinary work strategy, which included field-structural analysis, drone-shot high-resolution aerial photogrammetry, and geophysical prospecting, was employed to investigate whether the identified deformations may represent the ground effects of a previously unknown large earthquake in the area. Among the unearthed remains, some mosaics and a stone-paved monumental avenue show evidence of tectonic deformation, being fractured, folded, and uplifted. The trend of folding and fracturing is consistent with the NNW–SSE oriented tectonic max stress axis to which Western Sicily is currently subjected. Displacement along a fracture deforming the Decumanus Maximus together with the finding of a domino-type directional collapse, enable us to interpret the observed deformation as the ground signature of a coseismic slip. The seismic rupture occurred along a previously unmapped deformation front that fits well within the seismotectonic context of Western Sicily. Measured offset, geophysical prospecting, and age-constraints all suggest the possibility that a highly-energetic earthquake nucleated in the area following a coseismic rupture along a NE–SW trending back-verging reverse fault towards the end of the fourth century CE. Since seismic catalogs do not provide evidence of such a large earthquake, this event might represent a missed entry in the historical seismic record. This finding provides constraints to redefine the seismic hazard of Western Sicily, a region where recurrence-time intervals for large earthquakes are still unknown.

Submerged cultivation of Nigrospora sp. in batch and fed-batch modes for microbial oil production - Denise Tonato; Thiarles Brun; Luciana Luft; Maicon Sérgio Nascimento dos Santos; Fernanda Caroline Drumm; Patrícia Grassi; Jordana Georgin; Raquel C. Kuhn; Giovani L. Zabot; Marcio A. Mazutti (Natural Product Research, 2024)

Microalgae to biodiesel: A novel green conversion method for high-quality lipids recovery and in-situ transesterification to fatty acid methyl esters - Giuseppina Oliva; Antonio Buonerba; Alfonso Grassi; Shadi W. Hasan; Gregory V. Korshin; Antonis A. Zorpas; Vincenzo Belgiorno; Vincenzo Naddeo; Tiziano Zarra (Journal of Environmental Management, 2024)

Pantropical CO2 emissions and removals for the AFOLU sector in the period 1990–2018 - Sylvia S. Nyawira; Martin Herold; Kalkidan Ayele Mulatu; Rosa Maria Roman-Cuesta; Richard A. Houghton; Giacomo Grassi; Julia Pongratz; Thomas Gasser; Louis Verchot (Mitigation and Adaptation Strategies for Global Change, 2024)
Transparent, accurate, comparable, and complete estimates of greenhouse gas emissions and removals are needed to support mitigation goals and performance assessments under the Paris Agreement. Here, we present a comparative analysis of the agriculture forestry and other land use (AFOLU) emission estimates from different datasets, including National Greenhouse Gas Inventories (NGHGIs), FAOSTAT, the BLUE, OSCAR, and Houghton (here after updated H&N2017) bookkeeping models; Emissions Database for Global Atmospheric Research (EDGAR); and the US Environmental Protection Agency (EPA). We disaggregate the fluxes for the forestry and other land use (FOLU) sector into forest land, deforestation, and other land uses (including non-forest land uses), while agricultural emissions are disaggregated according to the sources (i.e., livestock, croplands, rice cultivation, and agricultural fires). Considering different time periods (1990–1999, 2000–2010, and 2011–2018), we analyse the trend of the fluxes with a key focus on the tropical regions (i.e., Latin America, sub-Saharan Africa, and South and Southeast Asia). Three of the five data sources indicated a decline in the net emissions over the tropics over the period 1990–2018. The net FOLU emissions for the tropics varied with values of 5.47, 5.22, 4.28, 3.21, and 1.17 GtCO 2 year −1 (for BLUE, OSCAR, updated H&N2017, FAOSTAT, and NGHGIs, respectively) over the recent period (2011–2018). Gross deforestation emissions over the same period were 5.87, 7.16, 5.48, 3.96, and 3.74 GtCO 2 year −1 (for BLUE, OSCAR, updated H&N2017, FAOSTAT, and NGHGIs). The net forestland sink was −1.97, −3.08, −2.09, −0.53, and −3.00 GtCO 2 year −1 (for BLUE, OSCAR, updated H&N2017, FAOSTAT, and NGHGIs). Continental analysis indicated that the differences between the data sources are much large in sub-Saharan Africa and South and Southeast Asia than in Latin America. Disagreements in the FOLU emission estimates are mainly explained by differences in the managed land areas and the processes considered (i.e., direct vs indirect effects of land use change, and gross vs net accounting for deforestation). Net agricultural emissions from cropland, livestock, and rice cultivation were more homogenous across the FAOSTAT, EDGAR, and EPA datasets, with all the data sources indicating an increase in the emissions over the tropics. However, there were notable differences in the emission from agricultural fires. This study highlights the importance of investing and improving data sources for key fluxes to achieve a more robust and transparent global stocktake.

How natural and anthropogenic factors should drive microplastic behavior and fate: The scenario of Brazilian urban freshwater - Fernando F. Sodré; Imisi M. Arowojolu; Maria C. Canela; Rodrigo S. Ferreira; Andreia N. Fernandes; Cassiana C. Montagner; Cristiane Vidal; Mariana A. Dias; Gilberto Abate; Leticia C. da Silva; Marco T. Grassi; Crislaine Bertoldi; et al. (Chemosphere, 2023)

Extracting light rare earth elements by applying electric field assisted mining technique - Carolina M.G. Pires; Haroldo A. Ponte; Marco T. Grassi; Maria José J.S. Ponte; Alexandra B. Ribeiro (Minerals Engineering, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Vibration control systems in a building prototype: Application of SMA coil springs in diagonal bracing and TMD - Yuri J.O. Moraes; Marcelo C. Rodrigues; Antonio A. Silva; Estephanie N.D. Grassi; Carlos J. Araújo (Engineering Structures, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Lanostanoid triterpenes from the fungus Rigidoporus microporus - Yuliet A. Rincón; Gastón E. Siless; Lucía Daniela Amado; María Virginia Dansey; Emanuel Grassi; Nahuel Schenone; Gabriela M. Cabrera (Natural Product Research, 2021)

A quick combined approach for the characterization of a cliff during a post-rockfall emergency - G. Pappalardo; S. Mineo; S. Imposa; S. Grassi; A. Leotta; F. La Rosa; D. Salerno (Landslides, 2020)

Solid wastes from the enzyme production as a potential biosorbent to treat colored effluents containing crystal violet dye - Patrícia Grassi; Fernanda C. Drumm; Stéfani S. Spannemberg; Jordana Georgin; Denise Tonato; Marcio A. Mazutti; Janaína O. Gonçalves; Marcos L. S. Oliveira; Guilherme L. Dotto; Sérgio L. Jahn (Environmental Science and Pollution Research, 2020)

Application of Beauveria bassiana spore waste as adsorbent to uptake acid red 97 dye from aqueous medium - Jordana Georgin; Eliana Alves; Fernanda Drumm; Denise Tonato; Patrícia Grassi; Jeferson S. Piccin; Marcos L. S. Oliveira; Guilherme L. Dotto; Marcio A. Mazutti (Environmental Science and Pollution Research, 2019)

Potential of Cedrella fissilis bark as an adsorbent for the removal of red 97 dye from aqueous effluents - Jordana Georgin; Dison S. P. Franco; Patricia Grassi; Denise Tonato; Daniel G. A. Piccilli; Lucas Meili; Guilherme L. Dotto (Environmental Science and Pollution Research, 2019)

Association Between the Serum Uric Acid Levels and Lacunar Infarcts in the Elderly - F. Crosta; U. Occhiuzzi; G. Passalacqua; E. Occhiuzzi; A. Cimini; D. Grassi; C. Ferri; C. Marini; C. Borghi; G. Desideri (Journal of Molecular Neuroscience, 2018)

Acute inhibition of estradiol synthesis impacts vestibulo-ocular reflex adaptation and cerebellar long-term potentiation in male rats - Cristina V. Dieni; Aldo Ferraresi; Jacqueline A. Sullivan; Sivarosa Grassi; Vito E. Pettorossi; Roberto Panichi (Brain Structure and Function, 2018)

The excitatory/inhibitory input to orexin/hypocretin neuron soma undergoes day/night reorganization - Claudia Laperchia; Roberta Imperatore; Idris A. Azeez; Federico Del Gallo; Giuseppe Bertini; Gigliola Grassi-Zucconi; Luigia Cristino; Marina Bentivoglio (Brain Structure and Function, 2017)

Drosophila suzukii population response to environment and management strategies - Nik G. Wiman; Daniel T. Dalton; Gianfranco Anfora; Antonio Biondi; Joanna C. Chiu; Kent M. Daane; Beverly Gerdeman; Angela Gottardello; Kelly A. Hamby; Rufus Isaacs; Alberto Grassi; Claudio Ioriatti; et al. (Journal of Pest Science, 2016)

Tracking the invasion of the alien fruit pest Drosophila suzukii in Europe - A. Cini; G. Anfora; L. A. Escudero-Colomar; A. Grassi; U. Santosuosso; G. Seljak; A. Papini (Journal of Pest Science, 2014)

Assessment of sweet potato [ Ipomoea batatas (L.) Lam] for bioethanol production in southern Italy - A. Montefusco; M. Durante; S. Grassi; G. Piro; G. Dalessandro; M. S. Lenucci (Plant Biosystems, 2014)

Isometric strength training lowers the O2 cost of cycling during moderate-intensity exercise - Jerzy A. Zoladz; Zbigniew Szkutnik; Joanna Majerczak; Marcin Grandys; Krzysztof Duda; Bruno Grassi (European Journal of Applied Physiology, 2012)

Genetic diversity in the endangered Sicilian endemic Brassica rupestris : Proposals for a conservation strategy - F. M. Raimondo; A. Scialabba; G. Zecca; F. Grassi; G. Casazza; L. Minuto (Plant Biosystems, 2012)

Sequence analysis of human rotavirus strains: comparison of clinical isolates from Northern and Southern Italy - T. Grassi; F. Bagordo; A. Cavallaro; M. Guido; C. Malaventura; G. Gabutti; A. Donno (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Slow $$ \dot{V}{\text{O}}_{2} $$ kinetics during moderate-intensity exercise as markers of lower metabolic stability and lower exercise tolerance - Bruno Grassi; Simone Porcelli; Desy Salvadego; Jerzy A. Zoladz (European Journal of Applied Physiology, 2011)

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)
Overviewing the European carbon (C), greenhouse gas (GHG), and non‐GHG fluxes, gross primary productivity (GPP) is about 9.3 Pg yr −1 , and fossil fuel imports are 1.6 Pg yr −1 . GPP is about 1.25% of solar radiation, containing about 360 × 10 18 J energy – five times the energy content of annual fossil fuel use. Net primary production (NPP) is 50%, terrestrial net biome productivity, NBP, 3%, and the net GHG balance, NGB, 0.3% of GPP. Human harvest uses 20% of NPP or 10% of GPP, or alternatively 1‰ of solar radiation after accounting for the inherent cost of agriculture and forestry, for production of pesticides and fertilizer, the return of organic fertilizer, and for the C equivalent cost of GHG emissions. C equivalents are defined on a global warming potential with a 100‐year time horizon. The equivalent of about 2.4% of the mineral fertilizer input is emitted as N 2 O. Agricultural emissions to the atmosphere are about 40% of total methane, 60% of total NO‐N, 70% of total N 2 O‐N, and 95% of total NH 3 ‐N emissions of Europe. European soils are a net C sink (114 Tg yr −1 ), but considering the emissions of GHGs, soils are a source of about 26 Tg CO 2 C‐equivalent yr −1 . Forest, grassland and sediment C sinks are offset by GHG emissions from croplands, peatlands and inland waters. Non‐GHGs (NH 3 , NO x ) interact significantly with the GHG and the C cycle through ammonium nitrate aerosols and dry deposition. Wet deposition of nitrogen (N) supports about 50% of forest timber growth. Land use change is regionally important. The absolute flux values total about 50 Tg C yr −1 . Nevertheless, for the European trace‐gas balance, land‐use intensity is more important than land‐use change. This study shows that emissions of GHGs and non‐GHGs significantly distort the C cycle and eliminate apparent C sinks.

Copper recovery from aqueous solution by a modified industrial polymer - Miriam A. Martins Alho; Diego Grassi; Alicia Fernández Cirelli; Norma B. D’Accorso (Environmental Chemistry Letters, 2009)

Phylogeographical structure and conservation genetics of wild grapevine - F. Grassi; M. Labra; S. Imazio; R. Ocete Rubio; O. Failla; A. Scienza; F. Sala (Conservation Genetics, 2006)

Chloroplast Microsatellites to Investigate the Origin of Grapevine - S. Imazio; M. Labra; F. Grassi; A. Scienza; O. Failla (Genetic Resources and Crop Evolution, 2006)

Comparison between recombinant baculo- and adenoviral-vectors as transfer system in cardiovascular cells - G. Grassi; H. Köhn; B. Dapas; R. Farra; J. Platz; S. Engel; S. Cjsareck; R. Kandolf; C. Teutsch; R. Klima; G. Triolo; A. Kuhn (Archives of Virology, 2006)

Ex-situ conservation of Black poplar in Europe: genetic diversity in nine gene bank collections and their value for nature development - V. Storme; A. Vanden Broeck; B. Ivens; D. Halfmaerten; J. Van Slycken; S. Castiglione; F. Grassi; T. Fossati; J. E. Cottrell; H. E. Tabbener; F. Lefèvre; C. Saintagne; et al. (Theoretical and Applied Genetics, 2004)

Evidence of a secondary grapevine domestication centre detected by SSR analysis - F. Grassi; M. Labra; S. Imazio; A. Spada; S. Sgorbati; A. Scienza; F. Sala (Theoretical and Applied Genetics, 2003)

Special Contribution: An Overview of Recent Seismic Refraction Experiments in Central Europe - A. Guterch; M. Grad; A. Špičák; E. Brückl; E. Hegedüs; G.R. Keller; H. Thybo; K. Aric; S. Acevedo; I. Asudeh; M. Behm; A. A. Belinsky; et al. (Studia Geophysica et Geodaetica, 2003)

Role of a Ca 2+ -activated K + current in the maintenance of resting membrane potential of isolated, human, saphenous vein smooth muscle cells - Milesi Verónica; Ernesto A. Aiello; Alejandro Rebolledo; Alicia Gomez Alvis; Angela O. Grassi de Gende (Pflügers Archiv - European Journal of Physiology, 1999)

Effect of different combinations of sparfloxacin, oxacillin, and fosfomycin against methicillin-resistant staphylococci - A. Ferrara; C. Dos Santos; M. Cimbro; G. Gialdroni Grassi (European Journal of Clinical Microbiology & Infectious Diseases, 1997)